Systematic metabolic engineering of Corynebacterium glutamicum for the industrial-level production of optically pure d-(−)-acetoin. Issue 23 (9th November 2017) - Mao, Yufeng; Fu, Jing; Tao, Ran; Huang, Can; Wang, Zhiwen; Tang, Ya-Jie; Chen, Tao; Zhao, Xueming
Abstract : Acetoin is a high-value-added industrial product and a promising bio-based platform chemical. Abstract : Acetoin is a high-value-added industrial product and a promising bio-based platform chemical. The two chiral enantiomers of acetoin are important potential pharmaceutical intermediates. However, at present it is very expensive to produce optically pure acetoin using conventional chemical synthesis methods. While classical biocatalysis fulfils many key criteria of green chemistry, it also comes with many other disadvantages, e.g. complicated process engineering, the need for expensive substrates and/or inducers, problematic production strains, or unsatisfactory titers. By redirecting metabolic fluxes, fine-tuning the activities of key enzymes and improving the strains' genetic stability, the systematically engineered strain CGR5 was constructed, which offered improvedd -(−)-acetoin production with optical purity surpassing 99.9%. Furthermore, acetoin production was increased significantly by the optimization of dissolved oxygen levels and culture medium components. Under aerobic conditions, the best strain CGR7 produced 96.2 g L −1 d -(−)-acetoin, with a productivity of 1.30 g (L h) −1 in a 5 L batch fermenter. To the best of our knowledge, this is the first report on producing optically pured -(−)-acetoin with the highest titer, without multi-stage fermentation, concentration of cells by centrifugation or other complicated process steps. The process therefore is efficient and environmentally friendly. These results furthermore demonstrate that the biosafety level 1 microorganism C. glutamicum is a competitive choice for industrial-level production of optically pured -(−)-acetoin.